2017
DOI: 10.1002/wsb.801
|View full text |Cite
|
Sign up to set email alerts
|

Predator guards on nest boxes improve nesting success of birds

Abstract: Humans have long provided nest boxes in a widespread and popular effort to augment nesting sites for cavity‐nesting birds. Nest boxes, however, may provide easy access for predators and thereby create ecological traps for nesting birds. Predator exclusion techniques are often deployed at nest boxes to reduce nest predation, but few studies have tested their performance. For the first time, we test the effectiveness of predator guards in promoting the nesting success of multiple species of birds at a large spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 51 publications
0
33
0
Order By: Relevance
“…Predation of eggs or chicks is the leading cause of nest failure in birds, with small rodents (Bradley and Marzluff 2003) and corvids (Marzluff and Neatherlin 2006) among the leading threats. The breeding success of cavity nesting species tends to be greater than that of species that build open cup nests (Wesołowski 2017), particularly if those species are nesting in boxes with antipredator guards provided by humans (Bailey and Bonter 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Predation of eggs or chicks is the leading cause of nest failure in birds, with small rodents (Bradley and Marzluff 2003) and corvids (Marzluff and Neatherlin 2006) among the leading threats. The breeding success of cavity nesting species tends to be greater than that of species that build open cup nests (Wesołowski 2017), particularly if those species are nesting in boxes with antipredator guards provided by humans (Bailey and Bonter 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, these same studies and others in the UK reported the opposite result of lower woodpecker predation rates in boxes for tits and Pied Flycatchers ( Ficedula hypoleuca ), relative to tree cavities [ 12 , 14 , 15 ]. As a result of higher predation rates in nest boxes, researchers often modify boxes to limit predation [ 35 , 36 ]. A recent analysis of nest fate data in nest boxes across the United States and Canada found that nest survival was improved with the presence of predator guards for most species examined, including Tree Swallows [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a result of higher predation rates in nest boxes, researchers often modify boxes to limit predation [ 35 , 36 ]. A recent analysis of nest fate data in nest boxes across the United States and Canada found that nest survival was improved with the presence of predator guards for most species examined, including Tree Swallows [ 36 ]. The presence of predator guards, therefore, might explain some discrepancies in reproductive success between birds nesting in boxes and tree cavities.…”
Section: Introductionmentioning
confidence: 99%
“…This reinforces the importance of creating (or maintaining) structurally complex habitats around artificial dens, to create less preferable habitat for cats. These findings, including observations of feral cat breeding within an artificial den, also highlight the importance of tailoring den dimensions (e.g., depth, entrance width) such that they exclude predators both from predating upon quolls within dens and using dens for their own recruitment (e.g., Bailey & Bonter, 2017). One possible reprieve for quolls is that cat and quoll activity overlap was lowest at artificial dens, suggesting a reduced probability of animals encountering one another outside of the den.…”
Section: Discussionmentioning
confidence: 89%